Statistieke vertel ’n storie: ’n Visie vir die Hervormde Kerk op pad na 2010 - T.F.J. Dreyer (HTS Teologiese Studies/Theological Studies, 2003)
Statistics tell a story: A vision for the Hervormde Kerk on its way to 2010 The aim of this article is to draw the outline of the “story” of the Hervormde Kerk by means of empirical research. Results drawn from statistics, both worldwide and local, combined with responses to a questionnaire survey within the Hervormde Kerk, point to certain characteristics and trends within the church. The article concludes with a vision for the church, on account of empirical and theological considerations.